Development of Novel Retainer Cleansing Products for During the Day Usage - Amornopparattanakul, Nattaporn; Pitaksuteepong, Tasana (Naresuan University Journal: Science and Technology (NUJST), 2017)
The aim of this study was to develop retainer cleansing products for during the day usage. These products were designed not only to remove saliva stain on the retainer surface, but also to provide clean and fresh smell and to be easy to carry around. The retainer cleansing products developed were alcohol and persulfate-free formulations and were prepared in two forms, including spray solutions and wet wipes. The spray solutions were first formulated by varying types and quantities of ingredients in the formulations. Then, good formulations, selected based on the homogeneity, clarity, color, odor, pH (ranging between 5.5-6.0), were subjected to stability testingusing accelerated conditions; including centrifugation test and temperature cycling test (6 cycles). The characteristics before and after stability test were compared. After that, the good characteristic and stable spray solution formulations were further used to prepare wet wipes. The wet wipes obtained were then subjected to stability test at 50°C, room temperature and 4°C for 2 weeks and evaluated for the changing of color, odor and weight. It was found that the four best spray solution formulations consisted of the following ingredients: water, glycerin, trehalose, PEG-40 hydrogenated castor oil, polyvinylpyrrolidone (PVP) K-30 and/or polyvinyl methyl ether/maleic acid (PVM/MA) copolymer, peppermint oil, parabens or potassium sorbate, triclosan, sorbitol, cetylpyridinium chloride, citric acidand sodium hydroxide.These selected formulations were then absorbed in spunlace non-woven fabrics. It was observed that the wet wipes did not change in color and odor after storing at 4°C, room temperature and 50°C. Moreover, their weight did not notably change. The preliminary cleaning test on retainer surface found that both spray solutions and wet wipes developed in this study could clear up all saliva stain and provided retainer with fresh-smelling and clean-looking. Keywords: Retainer, Spray solutions, Wet wipes
Keywords: Retainer, Spray solutions, Wet wipes